The International Labour Organisation’s Recommendation No. 198 and Self-Employed Workers - Hajn, Zbigniew (Acta Universitatis Lodziensis. Folia Iuridica, 2024)
The article discusses the legal situation of self-employed workers in international labour law. In particular, it focuses on the International Labour Organisation’s (hereafter: the ILO) predominant and clearly articulated approach in its Employment Relationship Recommendation, 2006 (No. 198), of dichotomising workers into employees and genuinely self-employed, and making the scope of their protection dependent on their belonging to one of these categories. The author questions whether this is the most appropriate way to provide protection to workers working under various forms of contractual arrangements other than the employment contract, including persons to be defined as “genuinely self-employed dependent workers.” A separate strand of consideration is the legal situation of genuinely and independently self-employed workers.